2016
DOI: 10.13005/bbra/2147
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Mineral and Vitamin Analysis of Fresh and Canned Tomato

Abstract: Many forms of preserved tomato are today available in the market. They range from dried, canned juiced and some other forms. These are to ensure nonstop supply of the fruit throughout the year and to prevent spoilage. However, in many cases; when a food item is subjected to the preservation techniques, they tend to lose some nutrients compared to the fresh food item. The current study aimed at comparing the nutritional contents of canned and fresh tomato obtained from the market. Proximate, mineral and vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 4 publications
8
29
3
Order By: Relevance
“…From a nutritional perspective, tomato is a good source of minerals and other elements [ 4 , 44 ]. In this review, 23 types of minerals and their amounts present in tomato are compiled, including the major elements (calcium, potassium, sodium, phosphorus, magnesium, sulfur, chlorine) and trace elements (iron, iodine, zinc, fluorine, cupper, manganese, cobalt, chromium, nickel, aluminum, arsenic, boron, lead, cadmium, nitrate, chlorine, selenium, silicon) ( Table 2 ).…”
Section: Nutritional Composition Of Tomatomentioning
confidence: 99%
See 2 more Smart Citations
“…From a nutritional perspective, tomato is a good source of minerals and other elements [ 4 , 44 ]. In this review, 23 types of minerals and their amounts present in tomato are compiled, including the major elements (calcium, potassium, sodium, phosphorus, magnesium, sulfur, chlorine) and trace elements (iron, iodine, zinc, fluorine, cupper, manganese, cobalt, chromium, nickel, aluminum, arsenic, boron, lead, cadmium, nitrate, chlorine, selenium, silicon) ( Table 2 ).…”
Section: Nutritional Composition Of Tomatomentioning
confidence: 99%
“…Tomatoes are used in many processed food products such as sauces, salads, soups, and pastes [ 2 ]. Common nutrients reported to be present in tomatoes are vitamins, minerals, fiber, protein, essential amino acids, monounsaturated fatty acids, carotenoids and phytosterols [ 3 , 4 , 5 , 6 ]. These nutrients perform various body functions including constipation prevention, reduction in high blood pressure, stimulation of blood circulation, maintenance of lipid profile and body fluids, detoxification of body toxins and maintaining bone structure as well as strength [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the maturity process, tomato fruit undergoes a series of nutritional, biochemical and physiological modifications which affect their functional and proximate quality characteristics ( Abdullahi et al, 2016 ). The instrumental assessment of these changes are preferred over the sensory evaluation, to minimize the tangential variations.…”
Section: Introductionmentioning
confidence: 99%
“…The OFSP flour had a high (61%) carbohydrate content; and this characteristic of the OFSP flour was expected because it is a starchy root.Since complementary foods are expected to be energy dense [19], this attribute of the OFSP flour makes it a suitable ingredient for developing foods.The carbohydrate percentage (61%) reported in this study was lower than those found by Laryea [20] and Dansby and Bovell-Benjamin [21] which were 83.29% and 90.6% respectively.The difference in carbohydrate content as cited by Laryea [20] and Dansby and Bovell-Benjamin [21] may be due to a difference in the variety of the sweet potato, the method of cultivation and the soil conditions under which the sweet potatoes were planted, as asserted by [22].The percentage of moisture recorded were relatively higher (27.5%) for tomato powder as shown in Fig. 2.This was not surprising because tomato is a fleshy vegetable, known to have a high water content [23]. Onion powder had 18.35% moisture, while anchovy powder had 7.6%.…”
Section: Development Of Complementary Foods For Infantsmentioning
confidence: 85%